Pintu Air Irigasi Elektromekanis Kombinasi Aliran Atas dan Bawah - Susi Hidayah; Aditya Prihantoko (Balai Teknik Irigasi, 2016)
Discharge adjustment in an essential activity in irrigation network. This commonly done using underflow irrigation gate (e.g. sliding gate) which have disadvantages regarding the hydraulic property of flow and floating debris. The overflow irrigation gate (e.g. skot beam) can overcome this but is difficult to operate. It is necessary to combine the important features of both structures so that the disadvantages can be avoided. This paper explains results on the development of double flow sliding gate with underflow and overflow combination which is designed to overcome the undesired hydraulic properties (energy loss) and inaccuracies of flow measurement because of sedimentation. The gate was designed to be easily operated using a solar powered electromechanical system that can be monitored and controlled remotely. Additionally, the gate also built using alternative materials that are GFRP honeycomb composite. The method used is laboratory and field tests on the designed double flow irrigation gate. Physical test results showed the value of materials qualified with predicted loading on the gate. The hydraulic test provided that the gate can predict discharge accurately during water level of 10, 20, and 30 cm. The gate can also control discharge effectively to fulfill fluctuating water balance needs in the service area. This results could be used as a reference to apply the concept of double flow sliding gate which is stated in the Indonesia Irrigation Planning Criteria 08, 2013.